Hermenêutica e Biodireito: a crise da fundamentação da decisão jurídica na resposta constitucionalmente adequada às questões bioéticas - Fiirst, Henderson (2019)
This thesis analyzes how the law analyzes and decides issues involving biotechnology and dominion of life. In order to do so, the research is based on the scientific development of the understanding of the ethical challenge of the sciences of such issues, with the formulation of Bioethics and, consequently, the doctrinal construction of Biolaw, a legal area dedicated to such questions. After this, criticism develops to the epistemological formulation of the Biological Right and its insufficiency to deal with the complexity of the problems presented by the biotechnology before the domain of the life, being developed in a Cartesian model of understanding of the Right, instead of being it in a paradigm post-positivist. Finally, we discuss the theory of legal decision in such cases, discussing the possibility of having only one correct answer for bioethical questions and the use of legal proceduralization as a decision making technique that reinforces the existence of only a correct answer to presented